Physicians' adherence to management guidelines for H. pylori infection and gastroesophageal reflux disease: a cross-sectional study - Wasef Na'amnih; Amir Ben Tov; Amna Bdair-Amsha; Shlomi Cohen; Judith Tsamir; Gabriel Chodick; Khitam Muhsen (BMC, 2020)
Abstract Background Primary care physicians (PCPs) play a pivotal role in the management of illnesses of the digestive tract. The study aim was to assess the adherence of PCPs to the guidelines on the management of Helicobacter pylori (H. pylori) infection and gastroesophageal reflux disease (GERD) in adults. Methods We conducted a cross-sectional study during March-July 2017 using the survey platform of Maccabi Healthcare Services in Israel. The study questionnaire assessed adherence to the Maastricht/Florence guidelines on H. pylori infection and the American College of Gastroenterology guidelines on the management of GERD. We sent the study questionnaires to a random sample of 610 PCPs via electronic mails. We contacted those who did not respond by telephone; eventually 180 physicians completed the survey. Results Ninety (50%) and 60 (36%) of the responders reported using professional guidelines for the diagnosis and management of H. pylori infection and GERD, respectively. Of the 180 participants, 153 (85%) reported referring patients with suspected peptic ulcer disease to H. pylori testing, 109 (61%) reported referring patients with unexplained iron deficiency anemia and 83 (46%) refer relatives of gastric cancer patients. In caring for young patients who have dyspepsia without alarm symptoms, 127 (74%) reported referral to a urea breath test for the diagnosis of H. pylori infection, and 136 (81%) referral to a specialist in gastroenterology if alarm symptoms present. Triple therapy with proton pump inhibitors/clarithromycin/amoxicillin or metronidazole was reported as first-line therapy by 141 (83%) participants. For GERD, 94-98% of the participants followed the appropriate recommendations. Conclusions We identified gaps between the practices of PCPs and the guidelines on H. pylori infection management, while guidelines on GERD management are well adopted. Simplification of the guidelines and exploring barriers towards their implementation by PCPs is warranted.